The effect of aggregate on the age at cracking of bonded concrete overlays subjected to restrained deformation - Dittmer, Thomas James (Department of Civil Engineering, 2015)
The need for effective and comprehensive repair techniques is increasing throughout the world as existing concrete structures continue to age. The bonded concrete overlay method, where a new repair material layer is cast over an existing damaged substrate, is the most commonly utilized method of repair. However, this repair technique is prone to failure due to differential volume changes between the newly cast repair material and the existing substrate. These volume changes can be attributed to thermal and shrinkage differences, with drying shrinkage being identified as they key source of the volume change. When the resulting induced stress form the differential volume changes exceeds the intrinsic tensile strength of the repair material, cracking failure occurs. This can be detrimental to the effectiveness of the repair and its durability. Overlay crack resistance has been found to be dependent on specific material properties, namely: tensile strength, elastic modulus and shrinkage. The effect of tensile relaxation on overlay performance is also significant, with the resulting 'stress relief' cause by this relaxation prolonging the time to cracking failure. In this investigation, the influence of the inclusion of coarse aggregate in the repair material is investigated. The study focuses on the specific impact of coarse aggregate volume content and size on the performance of bonded overlay materials, and the material properties that influence this performance. Two laboratory concrete mixes, with a w:c = 0.45 and 0.6, and a commercial repair product were tested with varying coarse aggregate volume contents. Further testing was conducted with w:c = 0.6 laboratory mixes with different nominal sized coarse aggregates. The impact of coarse aggregate volume and size on individual material properties, which included tensile strength, tensile relaxation, free drying shrinkage and elastic modulus, were tested separately for the various mixes. In conjunction with this, direct restrained shrinkage tests were conducted using ring tests to measure the influence of coarse aggregate volume and size on the time to cracking failure and crack intensity of the repair materials.